Changes over time in near‐saturated hydraulic conductivity of peat soil following reclamation for agriculture. Issue 2 (11th September 2019) - Hyväluoma, Jari; Räty, Mari; Kaseva, Janne; Keskinen, Riikka
Abstract: Reclamation of peat bogs for agriculture changes the physical and chemical characteristics of the peat matrix, for example, drainage and tillage accelerate decomposition, altering peat porosity, pore size distribution, and hydraulic properties. This study investigated changes in near‐saturated hydraulic conductivity over time after drainage of peat soil for agricultural use by conducting tension infiltrometer measurements in a mire that has been gradually drained and reclaimed for agriculture during the past 80 years (with fields drained 2, 12, 40, and 80 years before the measurements). At pore water pressure closest to saturation (pressure head −1 cm), hydraulic conductivity in the newest field was approximately nine times larger than that in the oldest field, and a decreasing trend with field age was observed. A similar (but weaker) trend was observed with −3 cm pressure head (approximately four times larger in the newest field in comparison to the oldest), but at −6 cm head, there were no significant differences. These results indicate that peat degradation reduces the amount of millimetre‐sized pores in particular. They also indicate that changes in peat macroporosity continue for several decades before a new steady state is reached. Abstract : Changes in near‐saturated hydraulic of peat soil were studied in a mire that has been gradually drained and reclaimed for agriculture during the past 80 years. Our results show that the near‐saturated hydraulic conductivity decreases rapidly after reclamation and that this transient phase may continue for decades before a new steady state with significantly lower hydraulic conductivity is reached. Our results indicate that peat degradation reduces the amount of millimetre‐sized pores in particular.